Sengketa Perikatan dalam Influencer Marketing: Ketika Endorsement Berujung Wanprestasi dan Persoalan Pembuktian Digital di Media Sosial - Clara Nuraini; Dzakyyah Ameizki Atmaja; Aqsal Ilham Saparullah (CV. ITTC INDONESIA, 2025)
The rapid growth of influencer marketing in Indonesia has transformed social media into a major platform for digital promotion. However, collaborations often carried out through electronic communication without a structured written agreement create legal challenges, particularly concerning breach of contract and digital evidence. This study examines the legal standing and evidentiary strength of electronic documents in proving breach of contract within influencer marketing agreements, as well as the legal responsibilities of the parties under the Indonesian Civil Code, the Electronic Information and Transactions Law, and consumer protection regulations. Using a normative juridical method and a descriptive-analytical approach, this research analyzes the legal norms governing digital contractual relations and reviews academic findings from relevant journals. The results indicate that digital evidence such as chats, direct messages, emails, and screenshots is legally admissible, but its effectiveness depends heavily on authenticity, integrity, and relevance. The absence of structured contracts complicates the proof of breach of contract because many agreements lack clear specifications of obligations. Legally, both influencers and business actors bear contractual, civil, and regulatory responsibilities, including the duty to provide accurate information to consumers. This study concludes that clear contractual arrangements, proper handling of electronic evidence, and good faith between parties are essential in resolving disputes within digital contractual relationships in Indonesia’s influencer marketing practices.